Efektifitas Pendidikan Kesehatan Tentang Hygiene Kewanitaan Terhadap Pengetahuan Dan Sikap Remaja Putri Dalam Menangani Keputihan - Wandha Paramitha Dhuangga; Misrawati ' (Jurnal Ners Indonesia, 2012)
The purpose of this study was to determine an effectiveness of health education about feminine hygiene toward knowledge andattitude of young women in handle of vaginal discharge issues. This research used quasy-experimental method with controlgroup which was divided into two groups. They were experimental and control group. The sampling technique used was stratifiedrandom sampling. 252 students were assign in this research which are divided evenly in experimental and control group. Thedata was analyzed using t-dependent test. The result show that there are significant diffrerences in the level of young women’sknowledge (p value = 0.000) and attitude (p value = 0.0034) in the experiment group after being given health education. Basedon this result, reseacher is suggesting school team that can work together with health care provider for giving a health educationespesially on health reproduction which could increase a knowledge and change behaviour in young women.Keywords : health education, feminine hygiene, knowledge, attitude, young women, vaginal discharge